Language and Difference: Heidegger, Saussure, and Derrida (Journal of the College of Languages (JCL), 2007)
Although the concept of difference is as old as the foundational concept of similarity, the modern (and contemporary) understanding of difference as a working notion that not only differentiates, but also approximates conflicting elements in an all encompassing system owes a great deal to the German philosopher Georg Wilhelm Friedrich Hegel (1770-1831). An idealist to the backbone, Hegel bequeathed to modern philosophy the postulation that the identity of an individual rests not in itself but in the relationship that individual‟s identity entertains with other members of society. In his classic Phenomenology of Spirit, Hegel explains how humans come to consciousness (pivotal concept in Idealism) through a strenuous, albeit apparently intuitive, process which he calls “the dialectic” that he exemplifies in the famous Master-Slave dialectic.1Hegel assumes that humans are not born with an independent, formative consciousness, but, on the contrary, they aspire to acquire self-consciousness when the self (which Hegel alternatively calls “being-for-self”) is acknowledged and recognized by other fellows—an arduous, but imperative, dynamic that Hegel terms “being-for-others.” Self-consciousness is attained only after the self104undergoes painstaking “stages” involved in the system of human relationships, which is representative of the Hegelian dialectic. This all-encompassing, ever changing system holistically places the individual “self” in relation to other “selves” while itself remains in constant motion. Accordingly, meaning and truth are never determinately fixed because they are always in process since, says Hegel, “the action has a double significance not only because it is directed against itself as well as against the other, but also because it is indivisibly the action of one as well as of the other.”2